2015
DOI: 10.1016/j.jenvman.2014.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Management considerations to minimize environmental impacts of arsenic following monosodium methylarsenate (MSMA) applications to turfgrass

Abstract: Monosodium methylarsenate (MSMA) is an organic arsenical herbicide currently utilized in turfgrass and cotton systems. In recent years, concerns over adverse impacts of arsenic (As) from MSMA applications have emerged; however, little research has been conducted in controlled field experiments using typical management practices. To address this knowledge gap, a field lysimeter experiment was conducted during 2012-2013 to determine the fate of As following MSMA applications to a bareground and an established tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Lower infield soil concentrations suggest that the arsenic compound was added to grassier areas for lawn treatment. Although, the organic arsenic compounds, such as MSMA, are considered less toxic than the inorganic forms, these methylated organic acids are considered carcinogenic and management practices for their use are heavily emphasized today [ 11 , 34 ]. In addition studies have shown that the organic MSMA compound may degrade to inorganic forms over time [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lower infield soil concentrations suggest that the arsenic compound was added to grassier areas for lawn treatment. Although, the organic arsenic compounds, such as MSMA, are considered less toxic than the inorganic forms, these methylated organic acids are considered carcinogenic and management practices for their use are heavily emphasized today [ 11 , 34 ]. In addition studies have shown that the organic MSMA compound may degrade to inorganic forms over time [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Effective January 2004, CCA-treated wood was no longer manufactured in the U.S. for residential uses, but its use to treat industrial wood products continues today. Arsenic has also been used historically as a pesticide for the control of insects (insecticides), as crop desiccants, and to control weeds (herbicides) [ 10 , 11 , 12 ]. Arsenic-containing insecticides include inorganic forms of lead arsenate, calcium arsenate, and copper acetoarsenite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize As loading to the environment, MSMA should be used as part of comprehensive management plans that utilize integrated pest management strategies such as lower application rates at optimal timings. Water management strategies that control irrigation and drainage and restrict application of MSMA in areas with a shallow water table or when heavy rains are forecasted can help reduce As runoff, leaching potential, and species conversion (Mahoney et al, 2015a). Additionally, food crops that accumulate As, such as rice and apples, should not be grown in areas where MSMA use was extensive (Abedin et al, 2002), and nonagronomic land uses for which human-soil contact probabilities are high, such as housing subdivisions, schools and playgrounds, should only be developed after monitoring and remediation have taken place.…”
Section: How Should Management Plans Account For Current and Potentiamentioning
confidence: 99%
“…In laboratory studies, many of which have used excessive MSMA loading rates and low soil‐solution ratios, rapid species transformation and redistribution of As from solid to aqueous phases have been observed (Shimizu et al, 2011a,b), whereas field research using recommended MSMA application rates has suggested tight cycling of As within the soil‐plant‐water system (Matteson et al, 2014; Mahoney et al, 2015b). Column and field studies evaluating As leaching potential following MSMA application have shown elevated porewater As concentrations to 40 cm depth but not to 76 cm in established turfgrass systems (Feng et al, 2005; Matteson et al, 2014; Mahoney et al, 2015a), although the extent of downward migration of As to groundwater depends on edaphic and management conditions. In Florida, the one state where MSMA use is now banned in turfgrass systems, elevated groundwater As (up to 815 μg/L) near golf courses and As accumulation in golf course lake systems have been reported (Wiegand 1999; Pichler et al, 2008).…”
Section: What Is the Ultimate Fate Of Arsenic Following Msma Applicatmentioning
confidence: 99%